Resolução de limites de funções trigonométricas com auxílio computacional - VILHENA, Cleison da Silva (2022)
The present work approached the resolution of limits involving trigonometric functions with computational aid to prove and visualize the results obtained analytically. In this sense, this approach began with a contextualization of the subject based on a brief account of the historical evolution of differential and integral calculus. In a second moment, the theory that governs the definition of limits, lateral limits, confrontation theorem and the fundamental trigonometric limit was presented. Subsequently, four problems of form, intuitive, algebraic and computational were solved, where in the last one an intrinsic function of the program wxMaxima was used linked to a geometric visualization.